Effect of temperature and light intensity on the growth of Eucheuma denticulatum seaweed branches from Van Phong Bay under laboratory conditions - Vu, Thi Mo; Le, Trong Nghia; Tran, Mai Duc; Le, Truong Trung Lien; Ho, Son Lam; Anirudhan, Anuraj (Vietnam Journal of Marine Science and Technology, 2026)
Establishing an initial source of tissue culture material is the first and most important step in the propagation process. To prepare for this stage, seaweed must be acclimatized in vitro for 4 to 8 weeks before sterilization. In this study, Eucheuma denticulatum seaweed branches were collected from seaweed farms operated by local households in Van Phong Bay, Dai Lanh commune, Khanh Hoa province, brought to the laboratory, and acclimatized in a controlled environment. Healthy branches with a glossy brown color were carefully selected, cut into 10–15 cm lengths, and fresh-weight 13–15 grams samples were tied to mesh frames and placed in glass tanks measuring 35 × 40 × 60 cm. Environmental factors such as temperature (22–30oC) and light intensity (40–200 µmol photons·m-2·s-1) were tested. The results showed that after six weeks of acclimation, E. denticulatum branches thrived best at 26oC, achieving a high survival rate of 73.33%, a fresh weight of 21.38 g, the highest cumulative growth rate of 1.12 %·day-1, and the lowest ice-ice disease prevalence at 1.11%. Similarly, after six weeks of acclimation, the branches showed optimal growth under specific light intensity conditions of 120 µmol photon·m-2·s-1, with a high survival rate of 77.78%, a fresh weight of 28.82 g, the highest cumulative growth rate of 1.77 %·day-1, and no occurrence of ice-ice disease. The E. denticulatum branches cultivated under optimal conditions are poised to serve as ideal raw materials for propagation through tissue culture techniques, paving the way for efficient production and the replacement of natural seaweed stocks.